Efficiency of higher education in the presence of shared inputs using data envelopment analysis - Gebru, Michael Gidey; Raza, Saqlain; Shaukat Khan, Mansoor (Penerbit Universiti Kebangsaan Malaysia, 2021)
This study measures the efficiency of higher education institutions with respect to teaching activity, research activity, and overall activities and also provides a direction for low-performing institutions to improve their performance. In many instances, the efficiency of the institution is a sum up of the efficiency of its activities. However, when the activities consume some resources in common, it requires the allocation of shared resources among the activities. Since sums up the efficiency of each activity does not give the institution’s overall efficiency, we use a joint data envelopment analysis that takes into account the institution’s internal operations to measure the teaching efficiency, research efficiency, and overall efficiency of the institutions. The empirical results indicate that the institutions that execute both activities simultaneously become more productive rather than adopt a single activity. Hence, this study suggests a useful and measurable action to improve the institution’s performance.